Positioning system for sensor less linear DC motor - Misron, Norhisam; Mat Saad, Ezril Hashim; Abdul Shukor, Fairul Azhar; Senan, Mahmud; Wakiwaka, Hiroyuki; Nirei, Masami (2007)
Sensor less Linear DC Motor (LDM) positioning system was designed to replace the expensive close loop linear DC motor system. The system was operating in open loop condition. Spring displacement and variant of PWM’s duty cycle in certain time was use to achieve the LDM required displacement. In this paper, sensor less positioning system for LDM had been proposed. The positioning expression and it performance had been studied. As the result, required position can be achieved using this system with 1mm accuracy.